2016
DOI: 10.1002/jclp.22282
|View full text |Cite
|
Sign up to set email alerts
|

Offline Versus Online Suicide-Related Help Seeking: Changing Domains, Changing Paradigms

Abstract: These findings show that the Internet has altered the suicide-related help-seeking paradigm. Online help seeking for suicidality was not more popular than face-to-face help seeking, even for emerging adults. However, treatment and prevention professionals have good reasons to increase their online efforts, because that is where some of the highest risk individuals are going for help with their most severe personal problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 45 publications
4
37
0
Order By: Relevance
“…One of the factors limiting prevention efforts is that "some desperately suicidal people… are likely to hide their true lethal feelings from the world" (Shneidman, 1994, p. 397). Such concealment highlights the need for early detection of suicidality, so that those in need can be directed towards professional help (Seward & Harris, 2016;Wahlin & Deane, 2012;Wilson, Rickwood, & Deane, 2007). Experts have recognised the dilemma of at-risk individuals not seeking help on their own and advocate for more empirical evidence for early detection of suicidality, such as warning signs and risk factors that can be used by clinicians and gatekeepers to identify those at current or potential risk (Hempstead & Phillips, 2014;Osteen, Frey, & Ko, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors limiting prevention efforts is that "some desperately suicidal people… are likely to hide their true lethal feelings from the world" (Shneidman, 1994, p. 397). Such concealment highlights the need for early detection of suicidality, so that those in need can be directed towards professional help (Seward & Harris, 2016;Wahlin & Deane, 2012;Wilson, Rickwood, & Deane, 2007). Experts have recognised the dilemma of at-risk individuals not seeking help on their own and advocate for more empirical evidence for early detection of suicidality, such as warning signs and risk factors that can be used by clinicians and gatekeepers to identify those at current or potential risk (Hempstead & Phillips, 2014;Osteen, Frey, & Ko, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lewiecki and Miller (2013) reported that 55% of suicide attempts are impulsive and not preceded by a great deal of planning, so there may not be time to connect the person at risk of suicide to those considered most capable of treating the causes of suicide, namely mental health providers. People at risk of suicide also tend to be more likely to reach out to personal contacts and relationships before seeking help from a professional (Seward & Harris, 2016). This suggests that suicide intervention training needs to be in the hands of friends, family members, and other trusted individuals who can guide the person toward additional help in a caring way.…”
mentioning
confidence: 99%
“…This study adds to the growing research suggesting that suicidal individuals may be more inclined to seek out help from online sources over face-to-face help (Seward & Harris, 2016;Wilks et al, 2018). Our findings revealed a discrepancy in online help-seeking preference between genders, with suicidal college women endorsing a significantly higher likelihood to seek out all varieties of online resources compared to men.…”
Section: Discussionmentioning
confidence: 45%
“…While treatment-engaging behavior among college students is low, the ubiquity of computing technology has given rise to novel methods of treatment delivery. In particular, emerging research has found promising results regarding interest in interventions delivered online for college students experiencing psychological distress and suicidal ideation (e.g., Lungu & Sun, 2016;Ryan, Shochet, & Stallman, 2010;Seward & Harris, 2016;Wilks, Coyle, Krek, Lungu, & Andriani, 2018). Online platforms may thus be leveraged to improve service receipt for suicidal college students.…”
mentioning
confidence: 99%
See 1 more Smart Citation